Thermal Stabilization study of polyacrylonitrile fiber obtained by extrusion - Robson Fleming Ribeiro; Luiz Claudio Pardini; Nilton Pereira Alves; Carlos Alberto Rios Brito Júnior (Polímeros, 2015)
A low cost and environmental friendly extrusion process of the Polyacrylonitrile (PAN) polymer was viabilized by using the 1,2,3-propanetriol (glycerol) as a plasticizer. The characterization of the fibers obtained by this process was the object of study in the present work. The PAN fibers were heat treated in the range of 200 °C to 300 °C, which is the temperature range related to the stabilization/oxidation step. This is a limiting phase during the carbon fiber processing. The characterization of the fibers was made using infrared spectroscopy, thermal analysis and microscopy. TGA revealed that the degradation of the extruded PAN co-VA fibers between 250 °C and 350 °C, corresponded to a 9% weight loss to samples analyzed under oxidizing atmosphere and 18% when the samples were analyzed under inert atmosphere. DSC showed that the exothermic reactions on the extruded PAN co-VA fibers under oxidizing synthetic air was broader and the cyclization started at a lower temperature compared under inert atmosphere. Furthermore, FT-IR analysis correlated with thermal anlysis showed that the stabilization/oxidation process of the extruded PAN fiber were coherent with other works that used PAN fibers obtained by other spinning processes.